Big data and the transformation of operations models: a framework and a new research agenda. Issue 11 (10th September 2017) - Roden, S.; Nucciarelli, A.; Li, F.; Graham, G.
Abstract: Big Data has been hailed as the 'next big thing' to drive business value, transform organisations and industries, and 'reveal secrets to those with the humility, willingness and tools to listen' (Mayer-Schönberger and Cukier, 2013: 5). However, despite growing interest from organisations across industry sectors, Big Data applications appear to have concentrated on delivering incremental change and operational efficiency improvements, with little evidence on using Big Data to facilitate strategic, transformational change. In this paper, we explore how Big Data can be used across different sectors in leading organisations and examine the ways in which it is fostering change in the core operations models of organisations. A definition of 'operations model' is developed and the core dimensions of an operations model are then examined, namely capacity, supply network, process and technology, and people development and organisation. Through a series of case studies, we examine the role of Big Data in affecting some, or all, of these dimensions in order to generate value for the organisation by optimising, adapting or radically transforming the operations model. Following our analysis, we develop a tentative framework which can be used both for understanding how Big Data affects operations models, and for planning changes in operations models through Big Data. We set out a new research agenda to systematically understand the full potential of Big Data in transforming operations models.